Bricklayers' output, 1945 (1945)
1945 1939-1945 "Bricklayers' output, 1945" [HFR0222], 1945 When newspaper articles suggested that the delays in dealing with the housing shortages caused by bomb damage were caused by union restrictions on the number of bricks that could be laid each day, Richard Coppock, General Secretary of the National Federation of Building Trades Operatives, issued this press release denying any union rules on output. However, a bonus payment scheme issued under Defence Regulations had laid down out targets.